Jesus freaks : stories of those who stood for Jesus : the ultimate Jesus freaks - DC Talk (Musical group); Voice of the Martyrs (Organization) (Tulsa, Okla : Albury Pub., 1952)
Christian recording group, dc Talk, captures the hearts of young people with this gripping compilation of stories about martyrs past and present. They tell of those who gave it all for God and are the ultimate Jesus Freaks. Young and old alike will ask themselves what they are trading their lives for!
Folded map on p. [3] of cover.
Includes bibliographical references (p. 362-368) and index.
Keywords: Persecution -- History; Christian martyrs -- History